Proteomic analysis of amniotic fluid for the diagnosis of fetal aneuploidies. (April 2011) - Kolialexi, Aggeliki; Tounta, Georgia; Mavrou, Ariadni; Tsangaris, George Th
Advances in technologies associated with mass spectrometry-based proteomic techniques have added a new dimension to the field of biomedical research. Most of the existing research on human gestation has focused on the application of these high-throughput methodologies in the study of amniotic fluid. In cases of fetal aneuploidies, the use of proteomic platforms has contributed to the identification of relevant protein biomarkers that could potentially change early diagnosis and treatment. The current article focuses on studies of normal amniotic fluid using proteomic technologies and describes alterations noted in the amniotic fluid proteome in the presence of fetal aneuploidies.